The Franciscan Order of Things: Empire, Community, and Archival Practices in the Monasteries of Ottoman Bosnia - Sekulić Ana (Comparative Southeast European Studies)
This article revisits the history of the Franciscan archives under Ottoman rule by focusing on archival documents, practices, and spaces in the Monastery of the Holy Spirit in Fojnica. Ottoman papers and archives preserved in the Franciscan spaces were often associated with Ottoman oppression. In this study, the author demonstrates that the documentary relationship between monasteries and Ottoman chanceries was not one-directional and cannot be characterized as oppressive. Franciscans actively engaged with the Ottoman documents and genres; they relied on the Ottoman vocabularies and legitimacy embedded in the documents, and subverted them at the same time, carving out their own physical and discursive spaces, which were tied to and yet different from the imaginaries of the Ottoman imperial order. The article emphasizes how examining archival narratives is located at the intersection of practices, texts, and spaces.